THE ROLE OF CULTIVAR IN IMPORT SUBSTITUTION (ON EXAMPLE OF VEGETABLE CROPS) - V. I. Burenin; A. M. Artemyeva (Овощи России, 2018)
Contribution of cultivar in a harvest formation is approximately 70%. State registered list of Russian Federation includes about 9 thousand cultivars and hybrids of vegetable crops and cucurbits belonging to 117 species, 55-60% from cultivars was created by Russian breeders. The features of Russian assortment: large genetic biodiversity of cultivars and hybrids in duration of period of vegetation, resistance to biotic and abiotic stressors; existence of cultivars with very large areal; high part of individual sector in a structure of space and gross (from 50-60 till 75- 85%). The crops that are insufficient objects of Russian breeding have been shown and they need to use import cultivars. In the article the most important breeding directions have been noted: on earliness, resistance to insects and diseases, adaptiveness, high nutritive quality, breeding of energetic effective cultivars, on heterosis, importance of quick reaction on market demands have been shown. For creation of import substituted cultivars they need to use of VIR worldwide collection of vegetable crops and cucurbits that consists of more than 52 thousand accessions. It includes about 30% landraces, 45-50% – modern cultivars and hybrids, 3-5% –primitive forms and wild species, and also hybrid populations, inbred and mutant lines, double haploid lines, accessions with identified genes and chromosome loci, controlling valuable traits. The problems of seed production in Russia and ways of their decision have been reflected: state economic support and state control, use of ecological factors in seed production.